Upregulated LINC01667 Expression Is Correlated With Poor Prognosis in Hepatocellular Carcinoma - Zhang, Kainan; Liu, Hui; Yu, Mengsi; Zhao, Hui; Yang, Ning; Bi, Xiaojuan; Sun, Li; Lin, Renyong; Lü, Guodong (Frontiers in Oncology, 2021)
The development of hepatocellular carcinoma (HCC) is a complex pathological process. Long intergenic non–protein-coding RNA 1667 (LINC01667, also known as MGC38584) plays an oncogenic role in several human cancers; however, its functional role in HCC tumorigenesis remains unknown. Here, we first evaluated the gene expression levels of LINC01667 in HCC using data from The Cancer Genome Atlas and Gene Expression Profiling Interactive Analysis (GEPIA) databases. We then elucidated the association between LINC01667 gene expression levels and the survival rates of patients with HCC. The effects of LINC01667 on the malignant phenotypes of HepG2 cells were studied using cell cycle, proliferation, Transwell migration, and Matrigel invasion assays. Based on data from the aforementioned databases and our experiments in vitro, we found that LINC01667 was overexpressed in HCC, and that patients with high LINC01667 levels had a remarkably poor overall survival rate. In addition, the inhibition of LINC01667 expression markedly suppressed HepG2 cell proliferation, migration, and invasion, and promoted HepG2 cell apoptosis in vitro. ChIRP-seq (chromatin isolation by RNA purification) showed that LINC01667 bound to MEG3, and downregulated the expression of MEG3. In addition, western blotting showed that LINC01667 could activate the NF-κB pathway to promote cancer progression. In conclusion, we report that LINC01667 is an important oncogene in HCC and may be used as a potential diagnostic and prognostic biomarker of HCC.